The Edinburgh companion to romanticism and the arts - McCue, Maureen; Thomas, Sophie (Edinburgh : Edinburgh University Press, 2023)
"From the birth of the museum to the explosion of mass-produced illustrated books, the Romantic period (c. 1770-1840) was a moment of rapid change and fruitful experimentation in the fields of art and literature alike. New advances in print production encouraged a wider range of readers to engage with literary forms that opened a path into the once aristocratic field of the visual arts. This Companion captures the way recent engagements with visual studies have reshaped how we approach and understand the boundaries between print and visual culture in the period. It brings together 27 research-led chapters that offer a detailed account of the productive, if sometimes tense, interactions between emergent forms of intermedial expression that were redefining culture in the Romantic period -- as they continue to do today" -- $$c Provided by publisher.
Frontmatter -- Contents -- Illustrations -- Acknowledgements -- Introduction -- Part I Perspectives -- 1 'The happiest vehicles of antiquarian knowledge': The Visual Arts and Romantic Antiquarianism -- 2 The Gothic Aesthetic: Word and Image -- 3 Aesthetic Landscapes: Travel and Tourism -- 4 Visualising the Indigenous Pacific -- 5 Elite and Popular Orientalisms -- Part II Exhibition, Commerce and Culture -- 6 Collecting and the Country House, 1750-1840 -- 7 Public Improvement as 'National Ornament': Commerce, Culture and Patriotism in London and Edinburgh -- 8 Commemoration, Domestic Display and the Decorative Arts: Romantic Nelsonia -- 9 Building(s) for Art: The Evolution of Public Art Galleries in England, 1780-1840 -- 10 Exhibitions Culture, Consumerism and the Romantic Artist -- 11 Portraiture: Commerce and Celebrity -- 12 Convergence and Dissonance: Romantic Theatre and the Visual Arts -- 13 Sound and Vision in Blake's London -- 14 Taken By Storm: Multisensory Learning in the Lecture Room -- 15 Romanticism, 'Real' Illusions and the Transformation of Experience in Modernity -- Part III Circulations: Print Culture and the Arts -- 16 Romantic Art and the Novel -- 17 Mired in Print: Romantic Writers and Caricature -- 18 'A Point to Aim at in a Morning's Walk': Encounters at the Print Shop -- 19 Illustrated Poetry in the Romantic Period -- 20 Fashioning the Female Artist: Allegory and Celebrity in Lady Diana Beauclerk's Watercolours of The Faerie Queene -- 21 Angelica Kauffman and the Sister Arts -- 22 Illustrated Magazines and Periodicals: Visual Genres and Gendered Aspirations -- Part IV Romanticism Reimagined, the 1830s and Beyond -- 23 Album Culture: Begging for Scraps -- 24 Nineteenth-Century Illustrated Poetry: Mise-en-Page and the Visual Rhythms of Seriality -- 25 Romantic Caricatures and Comics -- 26 Cultural Manifestations of Romanticism on the Contemporary Screen -- 27 Looking Back Through Fashion: Regency Romances and a 'Jumble of Styles' -- Notes on Contributors -- Index
Description based upon online resource; title from PDF title page (viewed Dec 19th, 2022).
Includes bibliographical references and index.
JSTOR
Keywords: Romanticism in art; Romanticism; Arts, Modern -- 18th century; Art and literature; Romantisme dans l'art.; Romantisme; Arts -- 18e siècle.; Art et littérature.; romanticism (form of expression); Romanticism in art; Arts, Modern; Art and literature; Romanticism; Literature: history & criticism; Literary studies: fiction, novelists & prose writers; Literary companions, book reviews & guides; Literature; 1700-1799; 1700-1899; Electronic book